2011
DOI: 10.1007/s11104-011-0954-0
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation mechanisms and subcellular distribution of Cu in maize grown on soil treated with [S, S]-ethylenediamine disuccinic acid

Abstract: Aims Many studies have proved that EDTA (ethylenediaminetetraacetic acid), EDDS ([S, S']-ethylenediamine disuccinic acid), and other chelating agents significantly enhance phyto-extraction of copper (Cu) from soil. However, some key factors, such as changes in membrane permeability of root cells and subcellular distribution of Cu and Cu-EDDS complex in leaves and roots, remain unresolved. Methods A pot-culture experiment was conducted using soil artificially contaminated with Cu to different degrees to compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…Moreover, EDDS is slightly toxic to plant roots (Fässler et al 2010). Upon EDDS application, plants may have suffered from the co-toxicity of Cu 2+ , EDDS, and the Cu-EDDS complex; the phytotoxicity has been demonstrated to be in the order Cu 2+ > EDDS > Cu-EDDS (Niu et al 2012). In the present study, the growth of both shoots and roots was significantly affected by the application of EDDS.…”
Section: Corn Growth and Cu Uptake Influenced By Eddsmentioning
confidence: 99%
“…Moreover, EDDS is slightly toxic to plant roots (Fässler et al 2010). Upon EDDS application, plants may have suffered from the co-toxicity of Cu 2+ , EDDS, and the Cu-EDDS complex; the phytotoxicity has been demonstrated to be in the order Cu 2+ > EDDS > Cu-EDDS (Niu et al 2012). In the present study, the growth of both shoots and roots was significantly affected by the application of EDDS.…”
Section: Corn Growth and Cu Uptake Influenced By Eddsmentioning
confidence: 99%
“…Some studies have indeed shown direct uptake of the complex, but at large (mM) concentration of complexes, mostly in phytoremediation studies. For instance, Niu et al (2012) found that copper (Cu) in plants grown on soil treated with [S, S]-ethylenediamine disuccinic acid (EDDS; lowest concentration 0.5 mmol/kg) was mainly as Cu-EDDS. At all concentrations, plant yield was significantly reduced, suggesting damage to the plants.…”
mentioning
confidence: 99%
“…This contrasts with the findings presented previously [ 7 ], where chelating agents appeared to be less damaging alone than when applied with equimolar Cu. The related chelating agent ethylenediamine- N , N ′-disuccinic acid (EDDS) has also been found to significantly increase both membrane permeability and cytoplasmic Cu levels, resulting in higher Cu accumulation in shoot tissue [ 12 ]. Organic acids including citric acid have previously been found to increase plasma membrane permeability to a greater extent than inorganic acids [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fine Pb deposits were observed in mitochondria, chloroplasts and within plasmodesmata [ 71 ]. In a recent study with Zea mays [ 12 ], the chelator EDDS was found to increase cell membrane permeability, with a concomitant increase in shoot concentrations. Although this was attributed to expansion of the apoplastic pathway through injured passage cells [ 72 ], rather than to increased solute entry into the symplast, it indicates that strong chelating agents can permeabilize plant cell membranes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation